English Teachers Professional And Pedagogic Competence Toward The Scientific Approach in Madrasah Aliyah In Jayapura City - Anggit Prasetio Nugroho; Erfin Wijayanti (Edumaspul: Jurnal Pendidikan, 2022)
The 2013 curriculum provides a new approach to the learning process in the classroom. A scientific approach is given to develop students' skills, knowledge, and attitudes. However, this scientific approach is a new challenge for teachers in its application. This challenge is indicated by the emergence of various issues related to the problems faced by teachers. The purpose of this study is to conduct a more in-depth search regarding the application of a scientific approach in the teaching and learning process carried out by English teachers at Madrasah Aliyah schools, Jayapura City. This research uses a type of qualitative research with descriptive methods. The sample in this study was an English teacher who taught at Madrasah Aliyah in Jayapura City. The research subjects were selected using a purposive sampling technique. In the application of the English learning process between the teachers of Darul Maarif Numbay Jayapura and Al-Muttaqin there are differences in their application. Among them, in the core activity procedures, Darul Maarif teachers mostly apply all core activity procedures. This proves that there is a need for follow-up in the form of training in the application of scientific theory in teaching English to teachers at Madrasah Papua.